Use of Complementary and Integrative Medicine in Women's Health: A Literature Review - Gülsen Müsteyde Altan Denizer; Nevin Hotun Şahin (Galenos Publishing House, 2024)
Complementary and integrative therapies have been used since the beginning of mankind. Their use has increased especially since the mid-20th century. In parallel to the development in diagnosis, treatment, and care, patients also want to be more involved in their treatments and are more inclined to prefer methods that alleviate their complaints. Reasons such as extended life expectancy, increase in degenerative and malign diseases, high costs of modern treatment methods, patients wanting to feel better psychologically, and symptom management have also led people to choose complementary and integrative medicine. In particular, the interest of women in these therapies has significantly increased. Women are more interested in these therapies because they have a wide range of gender-specific health issues, from premenstrual syndrome to dysmenorrhea, from infertility to pregnancy symptoms, and from postpartum depression to postmenopausal vasomotor symptoms. In their quest to find solutions to their problems, women have become more inclined to use complementary and integrative medicine. Nurses are aware of have knowledge and can evaluate complementary and integrative medicine to protect and improve women's health. This study presents a current literature review to evaluate the use of complementary and integrative medicine in women's health.